2020
DOI: 10.9734/cjast/2019/v38i630474
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Puddling Techniques in Sandy Loam Soil

Abstract: Aims: Puddling is a distinct operation to provide standing water condition for paddy cultivation. There are various puddling techniques conventionally adopted by the farmers. In order to scientifically establish the performance of various puddling techniques in terms of puddling quality, they were evaluated and compared. Study Design: The results were analyzed statistically using factorial experiment. Place: The study was carried out in the experimental field of Agricultural Engineering College &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A 15 cm diameter pipe filled with water was used, and the water level was recorded at 3-hour intervals to analyze the relationship between infiltration rate and duration. Analysis of variance for sandy loam soil puddling index revealed significance at the 1% level, with the power tiller-operated rotary tool exhibiting the highest puddling index [28,64,65]. The number of passes did not significantly affect the puddling index.…”
Section: Percolation Ratementioning
confidence: 82%
“…A 15 cm diameter pipe filled with water was used, and the water level was recorded at 3-hour intervals to analyze the relationship between infiltration rate and duration. Analysis of variance for sandy loam soil puddling index revealed significance at the 1% level, with the power tiller-operated rotary tool exhibiting the highest puddling index [28,64,65]. The number of passes did not significantly affect the puddling index.…”
Section: Percolation Ratementioning
confidence: 82%
“…Although there were no rational criteria to optimize the sedimentation period, the puddling sedimentation period differs from 1 to 4 days with respect to the structure of soil and the type of transplanter to be used. It was reported that for the smooth working of the paddy transplanter, a suitable puddling and sedimentation period from 2 to 72 h is required depending upon the type of soil (Dhiman et al, 2001; Hossen et al, 2017; Prasanthkumar et al, 2019). For example, in sandy loam soil, the sedimentation of heavy sand particles increases the resistance of the soil more quickly than in the case of light clay particles.…”
Section: Methodsmentioning
confidence: 99%